Pengaruh Fraksi Volume Serat Terhadap Kekuatan Tarik Komposit Serat Daun Nanas dan Sabut Kelapa dengan Polyester Bening 108 - Muhammad, M; Putra, Reza; Hafli, T; Islami, Nurul; Malik, Abdul (Malikussaleh Journal of Mechanical Science and Technology, 2023)
The goal of this study is to determine the effect of the matrix-to-filler ratio on the characteristic value of composites made from pineapple leaf fiber and coco fiber using clear polyester resin 108 as a matrix. The composite printing process involves combining 70% resin and 5% pineapple fiber: 15% pineapple fiber, 25% coconut fiber: 15% coconut fiber, 25% pineapple fiber, and 5% coconut fiber with 1% catalyst. The Hand-Lay Up method is used to create composites. Tensile strength testing mechanical properties are based on standards (ASTM D-3039). The tensile strength of 25% pineapple leaf fiber is the highest in this percentage variation: 5% coconut fiber with an average value of 44.88 MPa, 3.37% tensile strain, while pineapple leaf fiber 5% has the lowest tensile strength value: 25% coconut fiber with a 25.26 MPa average and a 2.54% tensile strain. According to the findings, the composite of 25% pineapple leaf fiber: 5% coconut fiber immersed in NaOH is suitable for use as an alternative tensile material.